2007
DOI: 10.1111/j.1460-9592.2006.02149.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway management using the pediatric GlideScope® in a child with Goldenhar syndrome and atypical plasma cholinesterase

Abstract: We report a case of difficult intubation in a child with Goldenhar syndrome and atypical plasma cholinesterase. Intubation attempts by direct laryngoscopy and the Trachlight were unsuccessful. The airway was ultimately secured using the pediatric GlideScope in conjunction with external laryngeal manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 15 publications
(22 reference statements)
2
31
0
Order By: Relevance
“…Several case reports have been published on this subject, all showing improved views or successful intubations compared with direct laryngoscopy. 10,11,14,15 In controlled trials in difficult pediatric airway scenarios, the results become somewhat controversial. Three studies are published on the use of the GlideScope in known or simulated difficult airway anatomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case reports have been published on this subject, all showing improved views or successful intubations compared with direct laryngoscopy. 10,11,14,15 In controlled trials in difficult pediatric airway scenarios, the results become somewhat controversial. Three studies are published on the use of the GlideScope in known or simulated difficult airway anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The GlideScope is part of the difficult airway equipment available in the pediatric and adult operating rooms at this institution and has been used in the expected and unexpected difficult pediatric and adult airway. 11 However, the GlideScope has been shown to have a rapid learning curve compared with intubation with a Macintosh blade. 20 Previous adult studies suggested a learning experience of 10 to 30 patients required for proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of FOB intubation and intubation with rigid bronchoscope was recently made, with good results for both techniques 5 . There is also a report on successful intubation with video laryngoscope in a child with Goldenhar syndrome 6 . According to the literature, LMA is successfully used in children with Goldenhar syndrome, especially for ophthalmic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Wald et al [4] also reported the successful use of the same blade in a three week old, 2.1 kg neonate after failed direct laryngoscopy. In pediatric patients, most of the published literature regarding VL focuses on its use in older children [5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%